2020
DOI: 10.1186/s12864-020-06959-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome and sex locus characterization in goldfish, Carassius auratus (Linnaeus, 1758)

Abstract: Background: Goldfish is an important model for various areas of research, including neural development and behavior and a species of significant importance in aquaculture, especially as an ornamental species. It has a male heterogametic (XX/XY) sex determination system that relies on both genetic and environmental factors, with high temperatures being able to produce female-to-male sex reversal. Little, however, is currently known on the molecular basis of genetic sex determination in this important cyprinid m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 54 publications
(103 reference statements)
1
28
0
Order By: Relevance
“…Our results may help elucidate the origin of sex-determination systems. Although it is difficult to observe heteromorphic sex chromosomes, sex-determining regions have been reported in several aquaculture animals (Wen et al, 2020;Xue et al, 2020). Liu et al (2018) obtained a male-specific sequence 8,661 bp in length from both bighead carp (Hypophthalmichthys nobilis) and silver carp (Hypophthalmichthys molitrix) via 2b-RAD-seq, and suggested that it was located on the Y chromosome or in a nascent Y-linked region.…”
Section: Discussionmentioning
confidence: 99%
“…Our results may help elucidate the origin of sex-determination systems. Although it is difficult to observe heteromorphic sex chromosomes, sex-determining regions have been reported in several aquaculture animals (Wen et al, 2020;Xue et al, 2020). Liu et al (2018) obtained a male-specific sequence 8,661 bp in length from both bighead carp (Hypophthalmichthys nobilis) and silver carp (Hypophthalmichthys molitrix) via 2b-RAD-seq, and suggested that it was located on the Y chromosome or in a nascent Y-linked region.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, hypoxia can turn genotypic females into phenotypic males and also upregulate the sex-determining gene dmy, which leads to a male-dominant population (Cheung et al, 2014). Besides, environmental sex determination effect also has been observed in many other fish species with GSD, such as Nile tilapia (O. niloticus) (Wang et al, 2017), goldfish (Carassius auratus) (Wen et al, 2020), and common carp (C. carpio) (Wu et al, 2003).…”
Section: Genotypic Sex Determination With Environmental Effectmentioning
confidence: 99%
“…Although some progress has been made in common carp, it is difficult to identify a clear signal for sex determination in this tetraploid species, in which sex determination is influenced by both genetic and environmental factors, and by epigenetic modifications 149–151 . An earlier study of goldfish characterized an 11.7‐Mb non‐recombining region likely located on the Y chromosome in male individuals 152 . Moreover, sex differentiation is commonly believed to be controlled by germ cells, 153,154 whereas in tetraploid goldfish, it appears to be controlled by somatic cells 155 .…”
Section: Genetic Basis Of Economically Important Traitsmentioning
confidence: 99%